Prevention of Tuberculosis cross infection; in the process of nursing care - Katanekwa, Situmbeko N.; Dahlback, Elizabeth (Asian Journal of Medical Sciences, 2016)
Nosocomial transmission of TB to healthcare workers (HCWs) is an issue of present interest. The Center for Disease Control and Prevention and the World Health Organization have recommended infection control measures such as respiratory isolation rooms with negative pressure for patients with productive cough and use of personal respiratory protective equipment ,i.e. respirators. Different infection control measures, usually administrative and engineering simultaneously, have been implemented in industrialized countries and resulted in reduced nosocomial tuberculosis transmission, (Jensen PA et al,2005).The implementation of all these measures maybe neither feasible nor cost-effective in resource-limited nations,(Harries AD et al,1997). In particular, engineering measures such as negative pressure isolation rooms with high efficiency particulate air (HEPA) filters maybe unaffordable. However scientifically proved modifications based on Infection Prevention and Control measures can be applied, and studies have proved their efficacy in resource-limited nations, (Lowbury Lecture, 2007).The study used Scientific Articles to; (1) highlight statistics and prevalence of occupationally contracted TB, (2)Discuss the preventive measures and their efficacy from multidisciplinary perspective and in the nursing care process, in developed and developing countries and (3)Emphasize the use of safe practice in nursing practice. Asian Journal of Medical Sciences Vol. 7(3) 2016 9-14